Discussões sobre a Educação de Jovens e Adultos na Escola Estadual Antônio de Azevedo em Jardim do Seridó/RN - Dantas, Jéssica Jennyfer Dias (2018)
The evaluation on the Education for young people and adults denotes as a factor of fundamental importance to improve student learning. It is necessary in this type of teaching that the act of evaluating starts on the teacher´s own self-assessment and get the student´s self-assessment, in which both can recognize the evaluation processes as procedures that favor the improvement of teaching-learning. Therefore, this monographic work aims to analyze if the evaluation instruments used by teachers from Antônio de Azevedo State School consider the student´s reality. Methodologically, the work consisted on a bibliographic research to authors like Barcelos (2014), Franco (2017), Luckesi (2011), Nascimento (2017) and others who discuss evaluation and youth and adult education.Furthermore, documentary research and field research with teachers in this teaching modality were also carried out. Starting from what was researched, it can be seen the little importance given to the assessment in this modality, having the need to pedagogical practices that attend the expectations and needs of each student from the Education for young people and adults that has its specificities and life stories.